1999
DOI: 10.1055/s-2007-973493
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Episodes of Coma: An Unusual Phenotype of Familial Hemiplegic Migraine with Linkage to Chromosome 1

Abstract: Over a period of ten years, a boy had several episodes of coma, lasting three to five days. Each episode was preceded by hemiparesis or paresthesias, aphasia, headaches and behavioural changes, with subsequent loss of consciousness. Partial seizures occurred during the first episode. A history of migraine or hemiplegic migraine was found in several members of the family. Linkage to chromosome 1q21-23, where a gene for familial hemiplegic migraine has been mapped, was shown in this family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 2 publications
1
29
1
Order By: Relevance
“…Last but not least, SD can directly precipitate seizure-like electrocorticogram activity, as first demonstrated by Leão (2). Consistent with our findings, epilepsy is more frequent in FHM patients than in the general population, with seizures occurring either during FHM attacks (71)(72)(73)(74) or interictally (75)(76)(77)(78). Epilepsy has been reported in many patients carrying FHM1 mutations (10,71,(79)(80)(81)(82).…”
Section: Figuresupporting
confidence: 91%
“…Last but not least, SD can directly precipitate seizure-like electrocorticogram activity, as first demonstrated by Leão (2). Consistent with our findings, epilepsy is more frequent in FHM patients than in the general population, with seizures occurring either during FHM attacks (71)(72)(73)(74) or interictally (75)(76)(77)(78). Epilepsy has been reported in many patients carrying FHM1 mutations (10,71,(79)(80)(81)(82).…”
Section: Figuresupporting
confidence: 91%
“…In addition, one family has been described in which FHM was linked to chromosome 1q, and the proband, but not the other affected family members, had hemiplegic migraine attacks associated with coma. 21 In all these families, however, the impairment of consciousness was short-lived and never as dramatic as in our patients with the S218L mutation; there also was no such dramatic delayed association with minor head trauma.…”
Section: Discussioncontrasting
confidence: 42%
“…A single familial hemiplegic migraine locus has been previously mapped to chromosome 19p13.1 [3][4][5][6][7][8][9][10][11][12][13]. Studies in different FHM families showed that additional causative genes must reside in other regions of the genome, including the long arm of chromosome 1 [5,8,9,12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Hemiplegia, which is associated in hemianesthesia, can involve the hemisome as a whole, or it can be localised in the upper part, involving in particular the face [3,5,[14][15][16]. During the attack, a state of confusion is often present and it can be compared to a psychotic state (visual or acoustic hallucinations) [5,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation